Access to success and social mobility through higher education : a curate's egg? - Billingham, Stuart (Great Debates in Higher Education, 2018)
This edited collection illuminates the benefits, drawbacks, challenges, opportunities of the push to widen access to success and social mobility through university and other post-secondary education experiences in the UK and internationally. It examines a range of particular case studies, and addresses issues including the role of part-time study, the experiences of BAME students, increasing access within rural communities, issues faced by those with mental health problems, and the role of employers. There has been some progress in some countries; increased access and enhanced success for some targeted populations, but not for others; and improvements in some regions of particular countries, but not for others. Efforts to improve access to success and social mobility, to strengthen the identification and nurturing of talent in every community and every corner of our societies, is, like the curates egg, only good in parts. This collection demonstrates that educational inequalities, unfairness and injustices still remain.